PERENCANAAN DAKWAH NAHDLATUL ULAMA (NU) DALAM MENANGKAL RADIKALISME DI KABUPATEN DELI SERDANG - Marwansyah, Marwansyah; Soiman, Soiman (Hikmah: Journal of Islamic Studies, 2025)
AbstractRadicalism poses a significant threat to diversity and social stability, necessitating well-structured da'wah planning to mitigate its spread. This study aims to analyze the da'wah planning conducted by Nahdlatul Ulama (NU) in combating radicalism in Deli Serdang Regency. Employing a qualitative field research approach, data collection was conducted through observation, interviews, and document analysis. Primary data were gathered from interviews with key informants, including the Deputy Secretary and the Head of Religious Affairs of PCNU Deli Serdang Regency. Secondary data were sourced from relevant academic journals and books. The findings revealed NU's structured da'wah planning involves: (1) implementing PKPNU (Education for NU Cadres), (2) strengthening Ahlussunnah wal Jama'ah (Aswaja) values, (3) promoting Harokah Nahdiyah (NU movements), (4) conducting Aswaja-based da'wah, (5) organizing the Ramadan Safari team with Aswaja-oriented clerics, (6) facilitating Friday sermons with Aswaja scholars, and (7) adopting educational approaches to disseminate NU teachings. This research highlights the importance of comprehensive da'wah planning that integrates religious teachings with social and educational aspects, providing practical recommendations for religious organizations to foster inclusive community harmony against radicalism.AbstrakRadikalisme merupakan ancaman nyata terhadap keberagaman dan stabilitas sosial sehingga diperlukan perencanaan dakwah yang terstruktur untuk menanggulanginya. Penelitian ini bertujuan menganalisis perencanaan dakwah Nahdlatul Ulama (NU) dalam menangkal radikalisme di Kabupaten Deli Serdang. Penelitian menggunakan pendekatan kualitatif dengan metode penelitian lapangan melalui observasi, wawancara, dan analisis dokumen. Data primer diperoleh dari wawancara informan kunci yaitu Wakil Sekretaris dan Ketua Bidang Keagamaan PCNU Kabupaten Deli Serdang, sementara data sekunder didapatkan dari jurnal dan buku relevan. Hasil penelitian menunjukkan perencanaan dakwah NU meliputi: (1) pelaksanaan Pendidikan Kader Penggerak Nahdlatul Ulama (PKPNU), (2) penguatan nilai-nilai Ahlussunnah wal Jama'ah (Aswaja), (3) Harokah Nahdiyah, (4) penerapan dakwah berbasis Aswaja, (5) Tim Safari Ramadhan dengan ustadz berfaham Aswaja, (6) pengajian khatib Jumat oleh ulama Aswaja, dan (7) pendekatan pendidikan dalam penyebaran ajaran NU. Penelitian ini menegaskan bahwa perencanaan dakwah yang efektif tidak hanya terfokus pada aspek keagamaan semata, tetapi juga memperkuat dimensi sosial dan pendidikan untuk menjaga keharmonisan masyarakat secara berkelanjutan dalam menghadapi radikalisme.